2019
DOI: 10.11591/ijeecs.v14.i3.pp1266-1271
|View full text |Cite
|
Sign up to set email alerts
|

A compact dual band PIFA antenna for GPS and ISM BAND applications

Abstract: This work deals with desgin of  a novel  compact  Dual band PIFA Antenna structure. The proposed antenna is validated for GPS and WIFI applications. The antenna is achieved on a lossy FR4 substrate. The final size of the antenna is 100×55×13.235 mm3. The final antenna structure was optimized and validated into simulation, fabrication and test. The proposed multiband PIFA is optimized by using solts technique. The fabricated antenna is validated to cover the operating frequencies of GPS (1.535 -1.7GHz) and BLUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The patch in [24] operates in two low-gain bands. Despite the fact that [25] antenna is minimal, it has two resonance frequencies: 1.65 GHz and 2.45 GHz with gain not exceeding 3.78 dB. When compared to the mentioned research, it's clear that the suggested antenna has a significant dimensions and gain advantages.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The patch in [24] operates in two low-gain bands. Despite the fact that [25] antenna is minimal, it has two resonance frequencies: 1.65 GHz and 2.45 GHz with gain not exceeding 3.78 dB. When compared to the mentioned research, it's clear that the suggested antenna has a significant dimensions and gain advantages.…”
Section: Resultsmentioning
confidence: 82%
“…WWAN/LTE smartphone applications using a decoupled multiband dual-antenna system by [24]. PIFA antenna operates in 3 frequency bands (1.53-1.70 GHz), (2.54-2.47 GHz) for mobile communications, including GPS, bluetooth, and WiFi was presented by [25]. Alibakhshikenari et al [26], a dual-polarized is suggested for use in 5G sub-6 GHz wireless networks with an average radiation efficiency of 82.6% and a gain of 7.5 dBi.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the benefits of compact size, simple structure, light weight, affordable price, flat, and multiband operation. It also replaces the use of multiple antennas for different resonant frequencies [4]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…The antenna array is a technique widely used by researchers to improve the gain and efficiency of the fift generation (5G) antenna. For instance, in the studies [13]- [21], the use of antenna arrays increased the gain and made the antenna radiation patterns more directional, in addition to some improvement in bandwidth. The aim of this work is to design a microstrip antenna printed on multilayer substrates in order to have a final proposed structure that functions at 28 GHz, and offers a high gain throughout the frequency bandwidth.…”
Section: Introductionmentioning
confidence: 99%